Pengaruh Kompensasi Finansial dan Non Finansial terhadap Kinerja Karyawan di Holiday Inn Resort Bali Benoa. - Paulina Tambunan; I Gusti Ngurah Widyatmaja; I Nyoman Jamin Ariana (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2022)
The decrease in performance can be influenced by the amount of compensation given by the hotel to employees. Providing compensation to employees is a motivation for employees to feel comfortable working at a hotel. A complaint states that employee performance needs to be considered so that a good compensation is needed at the Holiday Inn Resort Bali Benoa. The purpose of this study was to determine how the influence of financial and non financial compensation on employee performance at Holiday Inn Resort Bali Benoa. Data collection techniques through observation, interviews, questionnaires, and documentation. The type of data used is qualitative and quantitative data, while the data sources are carried out with primary and secondary data. Sampling was done through a random sampling technique with 32 question indicators and a total sample of 114 respondents. In this study, data analysis is used, namely qualitative data analysis and quantitative data analysis. Qualitative data analysis is by interview, observation and documentation. Quantitative data analysis is divided into descriptive statistics, namely Likert scale, and inferential statistics using validity, reliability and classical assumption tests, multiple regression analysis, T test, F test and coefficient of determination to prove the hypothesis and the relationship between independent variables with the dependent variable using SPSS version 25.0 for windows. Based on the research results obtained that financial compensation and non-financial compensation simultaneously affect employee performance. In addition, the results of the study that financial compensation (X1) and non-financial compensation (X2) partially have a significant and positive effect on employee performance. The determination value obtained is 57.5%, which means that employee performance is influenced by financial compensation and non-financial compensation by 57.5%. While the remaining 42.5% is influenced by other factors. Suggestions to the hotel to increase the number of programs that aim to improve employee teamwork. Keywords: Financial Compensation, Non Financial Compensation, Employee Performance